Hubungan Kecerdasan Emosional, Motivasi Belajar dan Dukungan Keluarga dengan Stres Akademik Siswa SMA Negeri 4 Mataram - Pusparini, Amilia; Adiwibawa, Danang Nur; Mahdaniyati, Aulia; Utary, Dewi (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2026)
Stres akademik pada siswa SMA sering dipicu ketidaksesuaian tuntutan belajar dengan kemampuan individu, dengan faktor psikososial sebagai prediktor utama. Penelitian ini menganalisis hubungan kecerdasan emosional, motivasi belajar, dan dukungan keluarga terhadap terjadinya stres akademik pada siswa SMA Negeri 4 Mataram. Menggunakan desain observasional analitik cross-sectional, sampel 99 siswa kelas X-XII diambil melalui proportionate stratified random sampling dari populasi 914 siswa. Instrumen terdiri dari Student Academic Stress Scale (SASS, 20 item, α=0,904), Student Emotional Intelligence Questionnaire (SEIQ, 8 item, α=0,880), Motivated Strategies for Learning Questionnaire (MSLQ, 31 item motivasi, α=0,93), dan Perceived Social Support from Family (PSS-Fa, 20 item, α = 0,752). Analisis univariat menggunakan frekuensi/persentase, bivariat menggunakan uji Chi-Square (SPSS 23, p < 0,05). Sebagian besar responden mengalami stres akademik rendah (54 responden, 54,5%), kecerdasan emosional tinggi (60 responden, 60,6%), motivasi belajar tinggi (50 responden, 50,5%), dan dukungan keluarga baik (48 responden, 48,5%). Terdapat hubungan signifikan kecerdasan emosional (p = 0,002), motivasi belajar (p = 0,013), dan dukungan keluarga (p=0,001) dengan stres akademik. Dukungan keluarga berperan sebagai faktor protektif terkuat terhadap stres akademik siswa SMA. The Relationship between Emotional Intelligence, Learning Motivation and Family Support with Academic Stress of Students at Mataram 4 State Senior High School Abstract Academic stress among high school students often arises from the mismatch between academic demands and individual capabilities, with psychosocial factors as primary predictors. This study analyzed the relationship between emotional intelligence, learning motivation, and family support with the occurrence of academic stress among students of SMA Negeri 4 Mataram. Employing an analytic observational cross-sectional design, a sample of 99 students from grades X-XII was selected via proportionate stratified random sampling from a population of 914 students. Validated instruments included Student Academic Stress Scale (SASS, 20 items, α=0.904), Student Emotional Intelligence Questionnaire (SEIQ, 8 items, α=0.880), Motivated Strategies for Learning Questionnaire (MSLQ motivation subscale, 31 items, α=0.93), and Perceived Social Support from Family (PSS-Fa, 20 items, α=0.752). Univariate analysis used frequency/percentage distributions, while bivariate analysis employed Chi-Square test (SPSS 23, p<0.05). Most respondents experienced low academic stress (54 respondents, 54.5%), high emotional intelligence (60 respondents, 60.6%), high learning motivation (50 respondents, 50.5%), and good family support (48 respondents, 48.5%). Significant relationships were found between emotional intelligence (p=0.002), learning motivation (p=0.013), and family support (p=0.001) with academic stress. Family support emerged as the strongest protective factor against academic stress among high school students.